2000
DOI: 10.1152/ajprenal.2000.278.6.f894
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase IV is expressed in H+-secreting cells of rabbit kidney

Abstract: Carbonic anhydrase (CA) IV is a membrane-bound enzyme that catalyzes the dehydration of carbonic acid to CO(2) and water. Using peptides from each end of the deduced rabbit CA IV amino acid sequence, we generated a goat anti-rabbit CA IV antibody, which was used for immunoblotting and immunohistochemical analysis. CA IV was expressed in a variety of organs including spleen, heart, lung, skeletal muscle, colon, and kidney. Rabbit kidney CA IV had two N-glycosylation sites and was sialated, the apparent molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 67 publications
(78 reference statements)
4
43
0
Order By: Relevance
“…Although it has been shown that the proximal tubule of trout, like that of mammals, is composed of discrete sections (e.g., P1 and P2 in fish) (1), we were unable to reliably distinguish P1 from P2 segments based on standard morphological criteria (thickness of the brush border and position of nuclei). In mammals, CA IV is expressed on the apical and basolateral membranes of S2 and S1 proximal tubules (36,46). The presence of tCA IV within the brush border of proximal tubules is consistent with the role of this segment of the nephron in reabsorbing the majority of HCO 3 Ϫ from the renal filtrate.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Although it has been shown that the proximal tubule of trout, like that of mammals, is composed of discrete sections (e.g., P1 and P2 in fish) (1), we were unable to reliably distinguish P1 from P2 segments based on standard morphological criteria (thickness of the brush border and position of nuclei). In mammals, CA IV is expressed on the apical and basolateral membranes of S2 and S1 proximal tubules (36,46). The presence of tCA IV within the brush border of proximal tubules is consistent with the role of this segment of the nephron in reabsorbing the majority of HCO 3 Ϫ from the renal filtrate.…”
Section: Discussionsupporting
confidence: 58%
“…In mammals, ϳ80 -90% of renal HCO 3 Ϫ reabsorption occurs within the proximal tubules. According to current models (42,48), filtered HCO 3 Ϫ combines with H ϩ , derived from an apical membrane sodium proton exchanger isoform 3 (NHE3) (65), to form CO 2 , a reaction that is catalyzed by membrane-bound carbonic anhydrase isoform IV (CA IV) (35,46). The newly formed CO 2 enters the proximal tubule cell where it is hydrated to H ϩ and HCO 3 Ϫ in the presence of CA isoform II (CA II) (59).…”
mentioning
confidence: 99%
“…IHC studies have revealed CA IV in basolateral membranes of proximal tubules of rat and rabbit kidney (Brown et al 1990;Schwartz et al 2000). In our recent IHC study, CA XIV protein was also present in basolateral membranes of the proximal tubules and in the initial portion of the thin descending limb of Henle (Kaunisto et al 2002).…”
Section: Discussionmentioning
confidence: 61%
“…It is interesting to note that six other GPIlinked proteins were identified in the non-fixed perfusion-biotinylated IMCDs. Of them, CD59 (38) and carbonic anhydrase IV (39) have been shown to be expressed in apical membrane of human and rabbit IMCDs.…”
Section: Discussionmentioning
confidence: 99%